Determinantes de la informalidad laboral en la ciudad de Riobamba, 2019. - María José, Pulla Miñaca (2020)
ABSTRACT: The objective of this study is to establish and analyze the determinants of labor informality in the city of Riobamba. Period 2019, where an econometric model of binary logistic regression was carried out. The information was from 137 surveyed people and included explanatory variables of labor informality, income, work experience, kinship, educational level, and age. Having as a result that the variables that have a positive relationship are income and kinship; while, educational level, age, and work experience present a negative correlation, thus evidencing the theory of human capital. The research comprises four sections. In the first section, we find the reference framework in which the introduction, the approach to the problem, and the objectives are developed; the second section includes the methodological framework and state of the art and the main approaches to labor informality. The third one shows the methodology of the research, the econometric model, and the analysis and discussion of results, and the fourth one comprises the conclusions and recommendations.